Externalities in knowledge production: Evidence from a randomized field experiment - Marit Hinnosaar; Toomas Hinnosaar; Michael Kummer; Olga Slivko (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Do contributions to online content platforms induce a feedback loop of ever more user-generated content or will they discourage future contributions? To assess this, we use a randomized field experiment which added content to some pages in Wikipedia while leaving similar pages unchanged. We find that adding content has a negligible impact on the subsequent long-run growth of content. Our results have implications for information seeding and incentivizing contributions, implying that additional content does not generate sizable externalities, neither by inspiring nor by discouraging future contributions.
Keywords: C93; L17; L86; 330; knowledge accumulation; user-generated content; Wikipedia